Corpo-Realities: Keepin’ It Real in “Music and Embodiment” Scholarship - McMullen, Tracy (Current Musicology, 2006)
In 1980, Abbie Conant, a white American trombonist living in Germany, won the solo trombone chair of the Munich Philharmonic, beating out thirty-two other candidates, all male. Invited to the audition via a letter addressed to Herr Abbie Conant, the trombonist achieved this success as a disembodied performer-from behind an auditioning screen. With the entire orchestra and director listening, as is the custom when auditioning solo chairs, Conant's sound was consumed as pure musical expression; indeed, her winning performance was exactly the realization the orchestra hoped for. However, when she stepped out from behind the screen, this seemingly unproblematic purity of sound was disrupted: for there stood a female body.